Challenging mindset : why a growth mindset makes a difference in learning -- and what to do when it doesn't - Nottingham, James; Larsson, Bosse, 1958- (Corwin, a SAGE Publishing Company, 2019)
Create the right conditions for a growth mindset to flourish in your school and your students Mindset doesn't matter when things are easy; it is only when faced with challenges that working from a growth mindset influences learning. But what is a 'growth mindset'? Why are mindset interventions not working in schools (yet)? What can be done to change this? Challenging Mindset answers key questions about Carol Dweck's theory of Mindset and shares proven strategies for putting mindset theory into practice. A nuanced understanding of mindset is critical for fostering a growth mindset in yourself,